2018
DOI: 10.3390/axioms7020039
|View full text |Cite
|
Sign up to set email alerts
|

What Do You Mean by “Nonlinear Eigenvalue Problems”?

Abstract: A nonlinear eigenvalue problem is generally described by an equation of the form F(λ, x) = 0, where F(λ, 0) = 0 for all λ, and contains by definition two unknowns: the eigenvalue parameter λ and the "nontrivial" vector(s) x corresponding to it. The nonlinear dependence of F can be in either of them (and of course in both), and also the research in this area seems to follow two quite different directions. In this review paper, we try to collect some points of possible common interest for both fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…For example, for A 3 = I n , one could search for solutions of the following type: X = αI n + βA + γA 2 . Now, (12) implies that (2αβ + γ 2 + α)A 2 + (α 2 + 2βγ + γ)A + (2αγ + β 2 + β)I n − D = 0. It can be shown that we can produce a large class of solutions in this way, if D is of a certain type.…”
Section: Remarkmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, for A 3 = I n , one could search for solutions of the following type: X = αI n + βA + γA 2 . Now, (12) implies that (2αβ + γ 2 + α)A 2 + (α 2 + 2βγ + γ)A + (2αγ + β 2 + β)I n − D = 0. It can be shown that we can produce a large class of solutions in this way, if D is of a certain type.…”
Section: Remarkmentioning
confidence: 99%
“…This problem is about the properties of the eigenvalues of the matrices A, B and C, where A + B = C. A good reference is the paper [11]. Note that if A is "small" then D − AXA could be regarded as a deformation of D. 12can be interpreted as a "generalized eigenvalue problem" (see, for example, [12]). 12is a type of Yang-Baxter matrix equation (see, for example, [13,14]) if D = O n and X = −Y.…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear eigenvalue problems of the type of Eq. ( 8) are frequently found in the mathematical literature, see [27] for a recent review. More details are provided in the Appendix A.…”
Section: Scalar Gravity Modelmentioning
confidence: 99%
“…For a recent review of some features of nonlinear operators and their eigenvalues, with applications to ordinary and partial differential equations, we refer the interested reader to [15].…”
Section: Introductionmentioning
confidence: 99%